Possibilistic instance-based learning - Hüllermeier, Eyke (Artificial Intelligence)

Flexibility and case-based evaluation in querying: An Illustration in an experimental setting - De Calmès, M.; Dubois, D.; Hüllermeier, Eyke; Prade, H.; Sèdes, F. (International Journal of Uncertainty, Fuzziness and Knowledge-Based Systems)

On the representation of fuzzy rules in terms of crisp rules - Dubois, D.; Hüllermeier, Eyke; Prade, H. (Information Sciences)

Sequential decision making in heuristic search - Hüllermeier, Eyke (Planning Based on Decision Theory (CISM Courses and Lectures No.472))

Possibilistic case-based decisions - Dubois, D.; Hüllermeier, Eyke; Prade, H. (Connectionist Approaches in Economics and Management Sciences)

Mining implication-based fuzzy association rules in databases - Hüllermeier, Eyke; Beringer, J. (Intelligent Systems for information processing: From representation to applications)

Handbuch Unternehmensnachfolge Recht - Basel II und Rating - Finanzierung - Fallbeispiele

Experiences from Teaching Software Development in a Java Environment - Breu, Ruth; Hellebrand, Sybille; Welzl, Michael

Einsatzbarrieren fuer Produktkonfiguratoren in der Automatisierungstechnik - Ergebnisse einer empirischen Untersuchung - Szydlowski, M.; Greve-Ecker, I.; Trier, Matthias (Industrie Management Journal 1/2003)

Anforderungen an die IT-Unterstuetzung für Communities of Practice im Unternehmen (in German) - Trier, Matthias (Industrie Management Journal)

Der 'Short-Clip' als Ansatz zur Produktion von video-basiertem E-Learning Content bei der VGU (in German) - Trier, Matthias; Herzog, Michael; Krallmann, Hermann (Proceedings Wirtschaftsinformatik 2003)

Integrating Communities of Practice with e-learning platforms to improve on-the-job-learning - Trier, Matthias (Proceedings of Organizational Knowledge, Learning and Capabilities Conference OKLC 2003, Barcelona, 13. April 2003.)
In knowledge intense business processes, a complex and dynamic body of knowledge is being built bottom-up by experience learning during exception handling and problem solving. Traditional qualification programs do not very effectively provide the special skills required. Communities of Practice are better supporting this dynamic on-the-job learning across hierarchies. Still, CoP approaches and platforms in many organisations can be improved by enriching them with e-learning components to create a connection between the unstructured personalisation strategy of CoPs and the structured training materials. Similarly, e-learning benefits from being linked to communities. In the article, the connections of both areas are analysed to derive a framework for integration. It proposes an agenda of activities for the two domains people-oriented and content-oriented integration of community management and e- learning. These two aspects affect the handling, configuration and design of software features. In a first stage, the challenge is mainly a management and organisational task. Consecutively, the integration processes can be further assessed in order to identify potentials for IT-automatisation.

IT-unterstuetztes Management virtueller Communities of Practice (in German) - Trier, Matthias (Proceedings DoIT Congress 2003, 24.11.2003)

Prototype implementation and performance evaluation of a QoS-conditionalized handoff scheme for mobile IPv6 networks - Neumann, Axel; Fu, Xiaoming; Karl, Holger (Computer Communications, 2003. CCW 2003. Proceedings. 2003 IEEE 18th Annual Workshop on)

Channel-Aware Schedulers For Voip And Mpeg4 For Wireless Communications - Aguiar, Ana Cristina Costa; Hoene, Christian; Klaue, Jirka; Karl, Holger; Miesmer, Horst; Wolisz, Adam (Proc. of 8th Intl. Workshop on Mobile Multimedia Communications (MoMuC'03))

Online scheduling for block-partitioned reconfigurable devices - Walder, Herbert; Platzner, Marco (Proceedings Design, Automation and Test in Europe Conference (DATE))

Fast online task placement on FPGAs: free space partitioning and 2D-hashing - Walder, Herbert; Steiger, Christoph; Platzner, Marco (Proceedings International Parallel and Distributed Processing Symposium)

Reconfigurable Hardware Operating Systems: From Design Concepts to Realizations - Walder, Herbert; Platzner, Marco (Proceedings of the 3rd International Conference on Engineering of Reconfigurable Systems and Algorithms (ERSA))

Heuristics for Online Scheduling Real-Time Tasks to Partially Reconfigurable Devices - Steiger, Christoph; Walder, Herbert; Platzner, Marco (Proceedings of the 13th International Conference on Field Programmable Logic and Applications (FPL))

Online scheduling and placement of real-time tasks to partially reconfigurable devices - Steiger, Christoph; Walder, Herbert; Platzner, Marco; Thiele, Lothar (Proceedings 24th IEEE International Real-Time Systems Symposium (RTSS))

Many-body and overlayer effects on surface optical properties - Bechstedt, F.; Del Sole, R.; Glutsch, S.; Hahn, P. H.; Pulci, O.; Schmidt, Wolf Gero (physica status solidi (b))

Gallium-rich reconstructions on GaAs(001) - Pristovsek, M.; Tsukamoto, S.; Ohtake, A.; Koguchi, N.; Orr, B. G.; Schmidt, Wolf Gero; Bernholc, J. (physica status solidi (b))

Cycloaddition reaction versus dimer cleavage at theSi(001):C5H8interface - Lu, Wenchang; Schmidt, Wolf Gero; Bernholc, J. (Physical Review B)

Layer-by-layer analysis of surface reflectance anisotropy in semiconductors - Castillo, C.; Mendoza, Bernardo S.; Schmidt, Wolf Gero; Hahn, P. H.; Bechstedt, F. (Physical Review B)

Nanowire-induced optical anisotropy of the Si(111)-In surface - Wang, Shuchun; Lu, Wenchang; Schmidt, Wolf Gero; Bernholc, J. (Physical Review B)

P-richGaP(001)(2×1)/(2×2)surface: A hydrogen-adsorbate structure determined from first-principles calculations - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F.; Pulci, O.; Del Sole, R. (Physical Review B)

Pyrrole (C4H4NH) and Polypyrrole Functionalized Silicon Surfaces Calculated from First Principles - Schmidt, Wolf Gero; Seino, K. (Surface Review and Letters)
The functionalization of the Si(001) surface by pyrrole and polypyrrole is investigated by means of first-principles pseudopotential calculations. We find dissociative reactions, leading to the partial fragmentation of the molecule, to be energetically most favored for pyrrole adsorption. The lowest-energy configuration for monolayer coverage is characterized by pyrrole rings bonded to the surface via Si–N linkage. In coexistence with adsorption geometries where both N and C are bonded to the surface, this structure accounts very well for the available experimental data. Chemisorption of pyrrole is found to effectively passivate the Si(001) surface, irrespective of the details of the adsorption geometry. The formation of well-ordered polypyrrole structures on Si(001) may require chemical modifications of the polypyrrole chains in order to account for the lattice mismatch.

Surface Ordering of P-rich InP(001): Hydrogen Stabilization vs Electron Correlation - Hahn, P. H.; Schmidt, Wolf Gero (Surface Review and Letters)
The influence of hydrogen on the reconstruction of InP(001) surfaces is studied by first-principles calculations. One-monolayer phosphorus forming oppositely buckled dimers with one hydrogen adsorbed per dimer is energetically favored for a wide range of surface preparation conditions. The electronic structure and STM image calculated for this adsorbate geometry agree well with the experimental findings obtained after annealing of MOVPE-grown InP samples. The Si(001)-like surface ordering as well as the surface band gap of more than 1 eV, supposedly arising from electron correlation effects [Li et al., Phys. Rev. Lett.82, 1879 (1999)], are naturally explained by the hydrogen-stabilized surface structure favored by the total-energy calculations.

Chemisorption of pyrrole (C4H4NH) on Si(001) calculated from first-principles - Seino, K.; Schmidt, Wolf Gero; Furthmüller, J.; Bechstedt, F. (Surface Science)

Uracil Adsorbed on Si(001): Structure and Energetics - Seino, K.; Schmidt, Wolf Gero; Preuss, M.; Bechstedt, F. (The Journal of Physical Chemistry B)

InP(001)-(2×1) Surface: A Hydrogen Stabilized Structure - Schmidt, Wolf Gero; Hahn, P. H.; Bechstedt, F.; Esser, N.; Vogt, P.; Wange, A.; Richter, W. (Physical Review Letters)

EfficientO(N2)method to solve the Bethe-Salpeter equation - Schmidt, Wolf Gero; Glutsch, S.; Hahn, P. H.; Bechstedt, F. (Physical Review B)

Chemisorption of pyrrole and polypyrrole on Si(001) - Seino, K.; Schmidt, Wolf Gero; Furthmüller, J.; Bechstedt, F. (Physical Review B)

Heidegger interprete del trascendentale - Ficara, Elena (Giornale Critico della Filosofia Italiana)

Logik als Organon: Erfindung des Neuen und Beherrschung der Komplexität in den Wissenschaften - Peckhaus, Volker (expressis verbis. Philosophische Betrachtungen. Festschrift für Günter Schenk zum fünfundsechzigsten Geburtstag)

Jean Nicod (1893–1924). Note biographique, Übersetzung von Max Kistler, Institut Nicod, Paris - Peckhaus, Volker
http://www.institutnicod.org/jn.htm (25.11.2003, am 24.08.2020 nicht mehr vorhanden)

The Pragmatism of Hilbert’s Programme - Peckhaus, Volker (Synthese (special issue “History of Logic”, ed. Juliette Kennedy/Gabriel Sandu))
Rezension: MR 2005b:03021 (E. Mendelson).

Novel Modulation Schemes Minimizing the Switching Losses of Sparse Matrix Converters - Schafmeister, Frank; Kolar, Johann (Proc. IEEE Annual Industrial Electronics Society Conference (IECON))

Evaluation of 1200V-Si-IGBTs and 1300V-SiC-JFETs for Application in Three-Phase Very Sparse Matrix AC-AC Converter Systems - Schafmeister, Frank; Herold, Simon; Kolar, Johann (Proc. 18th IEEE Applied Power Electronics Conf. (APEC))

Analytically Closed Calculation of the Conduction Losses of Three-Phase AC-AC Sparse Matrix Converters - Schafmeister, Frank; Baumann, Martina; Kolar, Johann (EPE Journal)

Evaluation of 1200 V-Si-IGBTs and 1300 V-SiC-JFETs for application in three-phase very sparse matrix AC-AC converter systems - Schafmeister, F.; Herold, S.; Kolar, J.W. (Eighteenth Annual IEEE Applied Power Electronics Conference and Exposition, 2003. APEC '03.)

Modeling and analysis of integrated magnetic components - Njiende, H.; Fröhleke, N.; Cronje, W.A. (IEEE 34th Annual Conference on Power Electronics Specialist, 2003. PESC '03.)

Coupled Pitch and Velocity Control of a Doubly-Fed Linear Motor, Beijing, China - Yang, B.; Meyer, M.; Grotstollen, H. (ISICT 2003, 5th International Symposium on Instrumentation and Control Technology)

Direct Torque Control of a Singled-sided Linear Induction Motor based on Sliding Mode - Yang, B.; Grotstollen, H. (The 4th International Symposium on LINEAR DRIVES FOR INDUSTRY APPLICATIONS (LDIA 2003), Austin Court, Birmingham, UK.)

Models of integrated magnetic components for simulation based design of SMPS with SIMPLORER - Njiende, H.; Wetzel, H.; Fröhleke, N.; Cronje, W. A. (10th European Conference on Power Electronis and Applications (EPE 2003), Toulouse, France)

Modelling of Integrated Magnetic Components for Power Electronics - Njiende, H.; Fröhleke, N.; Cronje, W. A. (EMF 2003, The 6th International Symposium on Electric and Magnetic Fields, Aachen, Germany)

Radio Based Control of a Linear Motor for the NBP Railway System - Pottharst, A.; Grotstollen, H. (ISICT 2003, 5th International Symposium on Instrumentation and Control Technology, Beijing, China)

Topologies for Low-voltage Regulator Modules - Wetzel, H.; Fröhleke, N.; Grotstollen, H. (ISICT 2003, 5th International Symposium on Instrumentation and Control Technology, Beijing, China)

Das Linearantriebssystem der NBP-Versuchsanlage - Schulz, B.; Yang, B.; Pottharst, A.; Grotstollen, H. (ISCoM 2003, International Scientific Colloquium on Mechatronics, Novocherkassk)

Bolzano, Bernard - Peckhaus, Volker (Lexikon der bedeutenden Naturwissenschaftler in drei Bänden, Bd. 1: A–E)

Carnap, Rudolf - Peckhaus, Volker (Lexikon der bedeutenden Naturwissenschaftler in drei Bänden, Bd. 1: A–E)

Boole, George - Peckhaus, Volker (Lexikon der bedeutenden Naturwissenschaftler in drei Bänden, Bd. 1: A–E)

Dingler, Hugo, Albert Emil Hermann - Peckhaus, Volker (Lexikon der bedeutenden Naturwissenschaftler in drei Bänden, Bd. 1: A–E)

Curry, Haskell Brooks - Peckhaus, Volker (Lexikon der bedeutenden Naturwissenschaftler in drei Bänden, Bd. 1: A–E)

George Boole, Selected Manuscripts on Logic and its Philosophy. hg. v. Ivor Grattan-Guinness/Gérard Bornet, Birkhäuser: Basel 1997 - Peckhaus, Volker (The Review of Modern Logic)

Eckart Menzler-Trott, Gentzens Problem. Mathematische Logik im nationalsozialistischen Deutschland. Mit einem Essay von Jan von Plato. Basel/Boston/Berlin: Birkhäuser 2001 - Peckhaus, Volker (Bulletin of Symbolic Logic)

Automatisierte Reglerinbetriebnahme für elektrische Antriebe mit schwingungsfähiger Mechanik - Schütte, F.

Dreiphasiger, netzfreundlicher Dreipunkt-Gleichrichter zur Speisung von Gleichspannungszwischenkreisen - Ide, P.

Antrieb mit doppeltgespeistem Linearmotor für ein spurgeführtes Bahnfahrzeug - Henke, M.

Born, Rainer, “Frege”, in: Stuart G. Shanker (Hg.), Routledge History of Philosophy, Bd. IX: Philosophy of Science, Logic and Mathematics in the Twentieth Century, Routledge: London 1996, 124–156 - Peckhaus, Volker (Mathematical Reviews)

Rossi, Arcangelo, “Kantianism and Physics from the 19th to the 20th Century”, in: Maria Luisa Dalla Chiara u.a. (Hgg.), Language, Quantum, Music. Papers of the 10th International Congress of Logic, Methodology and Philosophy of Science, Florence, Italy, August 1995, Dordrecht: Kluwer Academic Publishers 1999, 293–301 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Kraut, Robert, “Metaphysical Explanation and the Philosophy of Mathematics: Reflections on Jerrold Katz’s Realistic Rationalism”, In: Philosophia Mathematica (3) 9 (2001), 154–183 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Russell, Bertrand. "Einführung in die mathematische Philosophie. Mit einer Einleitung von Michael Otte, hg. v. Johannes Lenhard/Michael Otte", Felix Meiner Verlag: Hamburg 2002 (Philosophische Bibliothek; 536) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Stöltzner, Michael, “What Lakatos could Teach the Mathematical Physicist”, in: G. Kampis/L. Kvasz/M. Stöltzner (Hgg.), Appraising Lakatos: Mathematics, Methodology and the Man, Kluwer: Dordrecht 2002, 157–187 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Long, Jancis, “The Unforgiven: Imre Lakatos’ Life in Hungary”, in: G. Kampis/L. Kvasz/M. Stöltzner (Hgg.), Appraising Lakatos: Mathematics, Methodology and the Man, Kluwer: Dordrecht 2002, 263–302 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Wedin, M.V., “The Scope of Non-contradiction: a Note on Aristotle’s ‘Elenctic’ Proof in Metaphysics Γ 4”, In: Apeiron 32 (1999), no. 3, 231–242 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete [Reprint von MR 2002h:01004])

Congdon, Lee, “Lakatos’ Political Reawakening”, in: G. Kampis/L. Kvasz/M. Stöltzner (Hgg.), Appraising Lakatos: Mathematics, Methodology and the Man, Kluwer: Dordrecht 2002, 339–349 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Zahar, Ellie G.: “The Interdependence of the Core, the Heuristic and the Novelty of Facts in Lakatos’s MSRP”, In: Theoria. Segunda Epoca 16, No. 42 (2001), 415–435 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Köhler, E. u.a. (Hgg.), "Kurt Gödel: Wahrheit & Beweisbarkeit, Bd. 1: Dokumente und historische Analysen", öbv & hpt: Wien 2002 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Ganeri, Jonardon: “Objectivity and Proof in a Classical Indian Theory of Number”, In: Synthese 129 (2001), 413–437 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Tasic, Vladimir. "Mathematics and the Roots of Postmodern Thought", Oxford University Press: Oxford 2001 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Beckert, Herbert. "Zur Erkenntnis des Unendlichen", Leipzig/Stuttgart 2001 (Abhandlungen der Sächsischen Akademie der Wissenschaften zu Leipzig. Mathematisch-Naturwissenschaftliche Klasse. 59.3) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Martinich, A.P./Sosa, David (Hgg.), "A Companion to Analytic Philosophy", Blackwell Publishers: Oxford 2001 (Blackwell Companions to Philosophy) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Tait, W.W., “Remarks on Finitism”, In: Wilfried Sieg et al. (eds.), Reflections on the Foundations of Mathematics. Essays in Honor of Solomon Feferman, Natick, MA: A K Peters 2002, 410-419 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Nartonis, David K., “Locke-Stewart-Mill: Philosophy of Science at Dartmouth College, 1771-1854”, In: International Studies in the Philosophy of Science 15 (2001), 167-175 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hintikka, Jaakko, “Hyperclassical Logic (a.k.a. IF logic) and its Implications for Logical Theory”, In: Bulletin of Symbolic Logic 8 (2002), 404-423 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Wie hart ist die phraseographische Nuss? Überlegungen zu phraseologischen Wörterbü-chern aus der Sicht der ukrainischen Germanistik - Ptashnyk, Stefaniya (Jahrbuch Deutsch als Fremdsprache)

Rowe, David, “The Calm before the Storm: Hilbert’s Early Views on Foundations”, in: V.F. Hendricks et. al. (Hgg.), Proof Theory, Kluwer: Dordrecht 2000 (Synthese Library; 292), 55–93 - Peckhaus, Volker (Mathematical Reviews)

Sieg, Wilfried, “Toward Finitist Proof Theory”, in: V.F. Hendricks et. al. (Hgg.), Proof Theory, Kluwer: Dordrecht 2000 (Synthese Library; 292), 95–114 - Peckhaus, Volker (Mathematical Reviews)

Wolenski, Jan, “From Intentionality to Formal Semantics (from Twardowski to Tarski)”, In: Erkenntnis 56 (2002), 9–27 - Peckhaus, Volker (Mathematical Reviews)

Vollmar, Roland, „Seit wann gibt es Informatik?“, In: Abh. Braunschw. Wiss. Ges. 51 (2002), 25–47 - Peckhaus, Volker (Mathematical Reviews)

Parsons, Charles, “Realism and the Debate on Impredicativity, 1917-1944”, in: Wilfried Sieg/Richard Sommer/Carolyn Talcott (Hgg.), Reflections on the Foundations of Mathematics. Essay in Honor of Solomon Feferman, ASL: Urbana, IL 2002, 372-389 - Peckhaus, Volker (Mathematical Reviews)

Spalt, Detlef D., „Cauchys Kontinuum. Eine historiographische Annäherung via Cauchys Summensatz“, In: Archive for the History of Exact Sciences 56 (2002), 285–338 - Peckhaus, Volker (Mathematical Reviews)

Danneberg, Lutz, „Logik und Hermeneutik: die Analysis logica in den Ramistischen Dialektiken“, in: Terminigebrauch und Folgebeziehung, Logos: Berlin 1998, 129–157 - Peckhaus, Volker (Mathematical Reviews)

Lenhard, Johannes/Otte, Michael, „Analyse und Synthese – Von Leibniz und Kant zum Axiomatischen Denken“, Philosophia naturalis 39 (2002), 259–292 - Peckhaus, Volker (Mathematical Reviews)

Demopoulos, William, “On the Origin and Status of Our Conception of Number”, In: Notre Dame Journal of Formal Logic 41 (2000), 210–226 (2002) - Peckhaus, Volker (Mathematical Reviews)

Schirn, Matthias/Niebergall, Karl-Georg, “Extensions of the Finitist Point of View”, In: History and Philosophy of Logic 22 (2001), 135–161 - Peckhaus, Volker (Mathematical Reviews)

Rowe, David E., “Is (Was) Mathematics an Art or a Science”, In: Mathematical Intelligencer 24 (2002), No. 3, 59–64 - Peckhaus, Volker (Mathematical Reviews)

Vollmar, Roland, „Von Zielen und Grenzen der Informatik“, In: Abh. Braunschw. Wiss. Ges. 51 (2002), 9–24 - Peckhaus, Volker (Mathematical Reviews)

Neue Methoden und Publikationsformen in der Lexikologie/Lexikographie - Ptashnyk, Stefaniya (Wortverbindungen mehr oder weniger fest.Jhrbuch des Instituts für Deutsche Sprache 2003)

Statt einzelner Buchstaben ganze Texte zum Lesen und Schreibenlernen? – Gespräche über Schrift im frühen Anfangsunterricht. - Block, Iris (: Kinder schreiben und lesen. Beobachten – Verstehen – Lehren. Herausgegeben im Auftrag der deutschen Gesellschaft für Lesen und Schreiben als zehntes Jahrbuch der DGLS)

Wann lernen Kinder beim Vorlesen? - Block, Iris; Kruse , Norbert (Unterrichten mit Geschichten. Grundschulunterricht)

An ASM Based SystemC Simulation Semantics - Müller, Wolfgang; Ruf, Jürgen; Rosenstiel, Wolfgang (SystemC - Methodologies and Applications)
We present a formal definition of the event based SystemC V2.0 simulation semantics by means of distributed Abstract State Machines (ASMs). Our definition provides a rigorous and concise, but yet readable, definition of the SystemC specific operations and their interaction with the simulation scheduler that covers channel updates, notify, notify_delayed, wait, and next_trigger operations. We present the semantics in the form of rules by means of distributed ASMs reflecting the lines of the SystemC V2.0 Standard Manuals and reference implementation. The semantics introduced is defined to complement the language reference manual with aprecise definition reflecting an abstract model of the SystemC reference implementation, which can be used for advanced applications and for investigating interoperabilities with other languages.

Formal Semantics of Static and Temporal State-Oriented OCL Constraints - Flake, Stephan; Müller, Wolfgang (Journal on Software and System Modeling (SoSyM))
The textual Object Constraint Language (OCL) is primarily intended to specify restrictions over UML class diagrams, in particular class invariants, operation pre-, and postconditions. Based on several improvements in the definition of the language concepts in last years, a proposal for a new version of OCL has recently been published [43]. That document provides an extensive OCL semantic description that constitutes a tight integration into UML. However, OCL still lacks a semantic integration of UML Statecharts, although it can already be used to refer to states in OCL expressions. This article presents an approach that closes this gap and introduces a formal semantics for such integration through a mathematical model. It also presents the definition of a temporal OCL extension by means of a UML Profile based on the metamodel of the latest OCL proposal. Our OCL extension enables modelers to specify behavioral state-oriented real-time constraints. It provides an intuitive understanding and readability at application level since common OCL syntax and concepts are preserved. A well-defined formal semantics is given through the mapping of temporal OCL expressions to temporal logics formulae.
Keywords: Object Constraint Language UML Statecharts UML Profile Real-time constraints Temporal logics

Der Wechsel der Sprachen im Gehirn. Neue Einblicke in das ‚code-switching’ mittels funktioneller Kernspintomographie. - Behrent, Sigrid; Franceschini, Rita; Krick, Christoph; Reith, Wolfgang (Magazin Forschung der Universität des Saarlandes)

*Bernhard Pöll, Francophonies périphériques. Histoire, statut et profil des principales variétés du français hors de France. Paris: L’Harmattan 2001, 231p. - Behrent, Sigrid (Vox Romanica)

Der Umgang mit Formularen: Förderung der Lesekompetenz - Albers, Timm (Zeitschrift für Heilpädagogik)

[Rez. v.] Klaus Malettke/Chantal Grell (Hg.): Hofgesellschaft und Höflinge an europäischen Fürstenhöfen in der Frühen Neuzeit (15.–18. Jh.) [...]. Münster u.a. 2001 - Süßmann, Johannes (Historische Zeitschrift)
Keywords: Höfische Gesellschaft

[Rez. v.] Frauke Reitemeier: Deutsch-englische Literaturbeziehungen. Der historische Roman Sir Walter Scotts und seine deutschen Vorläufer (=Beiträge zur englischen und amerikanischen Literatur. 18). Paderborn u.a. Ferdinand Schöningh 2001 - Süßmann, Johannes (IASL online)
Keywords: Geschichtsroman; Scott; Walter; Naubert; Benedikte

[Rez. v.] Stefan Ehrenpreis / Ute Lotz-Heumann: Reformation und konfessionelles Zeitalter (=Kontroversen um die Geschichte), Darmstadt 2002 - Süßmann, Johannes (sehepunkte)
Keywords: Gedenken; Reformation